Splenic hydatid cyst: a case report - Adlakha, Dakshita; Chawla, Subhash; Utaal, Maneshwar S.; Sharma, Shivam; Khurana, Ankita; Thakor, Mrugen; Ramnani, Sakshi (International Surgery Journal, 2024)
Hydatid cyst (HD) disease is a parasitic infection caused by Echinococcus granulosus. It occurs worldwide, but its prevalence is higher in the rural communities where sheep and cattle raising constitute a crucial component of the agricultural industry. This is a zoonotic disease which spreads via close contact of humans with sheep and dogs. The most common organs involved in hydatid cyst are the liver and lungs. However, other organs may also foster it, such as the spleen which is a rare clinical condition, with an incidence rate of between 0.5% and 4%. In this study, a 46-year-old male with a primary splenic HC is reported with chief complaint of pain and non-tender palpable mass in left hypochondrium. A 9.7×10.6×11 cm splenic cystic mass was detected on ultrasonography (US) and confirmed by abdominal computed tomography (CT) scan, without involvement of other organs. Splenectomy was done along with excision of intact hydatid cyst. Pathological examinations revealed cystic hydatidosis. We describe this case of an isolated splenic HC, which was successfully treated with total splenectomy, focusing on the management and outcome of this disease.